The KORELASI ANTARA ANALISIS PROFIL WAJAH MENGGUNAKAN SEFALOMETRI (ANALISIS STEINER) DAN FOTOMETRI LATERAL (ANALISIS PROFFIT) DENGAN DATA PASIEN DI LABORATORIUM KLINIK FKG UB - Inggil, Darojat Arya; Silviana, Nur Masita (Fakultas Kedokteran Gigi UB, 2025)
Introduction: Facial profile analysis is crucial for evaluating aesthetics in orthodontic treatment planning.Cephalometry analysis (Steiner) assesses soft tissue structure through the S-line, while photometry lateralanalysis (Proffit) focuses on soft tissue angles with a more comprehensive approach. This study evaluates thecorrelation between these two methods in patients at the FKG UB Clinic. Objective: To determine thecorrelation between facial profiles assessed by Steiner’s cephalometric analysis and Proffit’s photometricanalysis at FKG UB Clinic. Methods: A cross-sectional study was conducted on 30 patients meeting theinclusion criteria (aged ≥17 years, regardless of prior orthodontic treatment, with high-quality lateralcephalometric and photometric data). Data were analyzed using the Spearman test. Results: The correlationcoefficient of 0.247 with a p-value of 0.188 (p > 0.05) indicated no significant relationship between the twomethods. Most results from both methods showed convex facial profiles, with some differences caused byphoto-taking techniques. Conclusion: There is no significant correlation between Steiner and Proffit analyses.However, both methods complement each other, and their combined use can improve the accuracy ofdiagnosis and orthodontic treatment planning.Keywords: Steiner analysis, Proffit analysis, cephalometry, photometry lateral, facial profile.